Exploring Challenges Faced by Women in Executive Leadership in the Non-Profit Sector in South Africa - Nsibande, Nondumiso (niversity of the Witwatersrand, Johannesburg, 2023)
Women continue to face challenges in executive leadership positions within non-profit organisations in South Africa which negatively affects their performance. Limited progress has been made on women’s representation in decision-making in the last few years, however, those who make it to these positions tend to vacate them because of obstacles that exist while holding these positions. This study used a phenomenological qualitative research design to explore the experiences of women in senior management positions in the non-profit sector. The study used in-depth interviews to collect qualitative data from 20 participants: 16 women leaders, and four men leaders in the non-profit sector. Feminist theory was used to understand the different challenges and discriminations faced by women in senior management based on race, gender, and other forms of stereotype. The study found that the main challenges faced by participants which affected their ability to thrive in their role as leaders in the organisations was the reinforcement of patriarchal ideologies, including gender norms in the workplace, lack of resources, lack of mentorship and investment in leadership training, gender wage inequality, discrimination based on the intersections between race and gender, and a lack of a family work-life balance. Participants also identified factors that could contribute to sustaining women in leadership positions such as positive organisational culture, and being intentional in challenging toxic gender norms and overall gender inequality; promoting work-life balance policies; investing in mentorship and networking opportunities, networking and leadership training
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Women; Executive leadership; Not for Profit; Challenges; Experiences; UCTD; SDG-5: Gender equality